Age and stimulus dependency of visually evoked cerebral blood flow responses - Pánczél, Gyula; Daffertshofer, Michael; Ries, Stephan; Spiegel, Dagmar; Hennerici, Michael G. (Stroke, 1999)
BACKGROUND AND PURPOSE: During visual stimulation, the increased metabolic demand is coupled with an increase of cerebral blood flow velocity (pCBFV) in the posterior cerebral artery (PCA). Investigation of the visually evoked flow responses (VEFR, expressed as percentage of increase from baseline pCBFV values) was suggested for different conditions of vasoneuronal disorders in the absence of any systematic investigation in healthy subjects. - METHODS: We investigated VEFRs from both PCAs to various increasingly complex paradigms (diffuse light, alternating checkerboard patterns, and a color video movie stimulation; 5, 10, 20, and 30-second intervals) in 60 healthy volunteers (mean age, 41.5+/-14.9 years; range, 24 to 80 years; 28 male, 32 female) at different recording sites (P1 versus P2 segments of PCAs). - RESULTS: With increasing complexity of stimulation, the VEFRs increased significantly (24.3+/-10.3%, 28.5+/-13.5%, and 43.4+/-10.7%, respectively). Twenty-second stimulation intervals yielded maximal responses (41.5+/-13.2%) compared with 5-, 10-, and 30-second intervals (22.6+/-14.1%, P=0.001; 34.4+/-11.7%, P=0.0042; and 35.5+/-9.9%, P=0.0032, respectively). Significantly higher responses were gained from P2 segments than from P1 segments (42.7+/-7.2% versus 28.2+/-7.1%). Although VEFRs tended to decrease in amplitude with age (mean, 41. 7+/-10.5% [20 to 40 years], 35+/-9.2% [40 to 60 years], and 33.9+/-8.6% [60 to 80 years]); without significant sex-related differences, only the percentage decrement of the pulsatility indices during stimulation were significant (mean, 24+/-10.7% [20 to 40 years], 20+/-7.3% [40 to 60 years], and 13+/-11.2% [60 to 80 years]). - CONCLUSIONS: For optimal stimulus conditions for maximum VEFRs, a colored video stimulation of 20-second intervals should be used to combine responses not only from the primary visual projection fields (V1 and V2) but also from temporal lobe areas (V3 through V5) often supplied by the PCA.
Gesehen am 28.07.2022